2019
DOI: 10.32731/smq.284.122019.01
|View full text |Cite
|
Sign up to set email alerts
|

Smart Sports Fans: Factors Influencing Sport Consumption on Smartphones

Abstract: Smartphones are playing pivotal roles in sports fans’ media consumption journey. However, what motivates sports fans to use smartphones for sports; what are some of the behavioral factors that influence sports consumption on smartphones; how smartphone use for sports is related to other media usage; and how fandom interacts with motivational and behavioral factors still remains unclear to academic scholars. An online survey ( n = 646) was conducted to uncover the factors influencing sports consumption on smart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…As we studied OTT users' actual usage, results showed that fandom was positively associated with the amount of time and money users spent on these services. This finding is in line with the studies that focused on sports fans' traditional media consumption (Gantz et al ., 2006) and smartphone usage (Chan-Olmsted and Xiao, 2019) where fans were found to be more likely than nonfans to consume sport media content. Unsurprisingly, sports fandom is also positively associated with the money they spent on these services.…”
Section: Discussionmentioning
confidence: 99%
“…As we studied OTT users' actual usage, results showed that fandom was positively associated with the amount of time and money users spent on these services. This finding is in line with the studies that focused on sports fans' traditional media consumption (Gantz et al ., 2006) and smartphone usage (Chan-Olmsted and Xiao, 2019) where fans were found to be more likely than nonfans to consume sport media content. Unsurprisingly, sports fandom is also positively associated with the money they spent on these services.…”
Section: Discussionmentioning
confidence: 99%
“…The main research is the meaning and status quo of current smart sports, not how to effectively develop smart sports. As a new type of sports, we should uphold the idea of lifelong sports [11][12]. Both Go and Chess are excellent traditional cultures of the Chinese nation and possess infinite artistic charm.…”
Section: Smart Sportsmentioning
confidence: 99%
“…However, the penetration of digital media also provides sports fans a new opportunity and platform to enhance their engagement with other fans. For instance, Chan-Olmsted and Xiao (2019) explained that when sports fans want to identify themselves with a social group, smartphones become a vital medium for these fans to connect with a sport teams through the interaction with other fans as a group. In addition to technologies and equipment, digital media platforms such as social media, forums, and team sites provide fans with more chances to get connected.…”
Section: Literature Reviewmentioning
confidence: 99%